2022
DOI: 10.1097/ccm.0000000000005674
|View full text |Cite
|
Sign up to set email alerts
|

Wellness and Coping of Physicians Who Worked in ICUs During the Pandemic: A Multicenter Cross-Sectional North American Survey*

Abstract: Few surveys have focused on physician moral distress, burnout, and professional fulfilment. We assessed physician wellness and coping during the COVID-19 pandemic.DESIGN: Cross-sectional survey using four validated instruments. SETTING:Sixty-two sites in Canada and the United States. SUBJECTS:Attending physicians (adult, pediatric; intensivist, nonintensivist) who worked in North American ICUs. INTERVENTION: None. MEASUREMENTS AND MAIN RESULTS:We analysed 431 questionnaires (43.3% response rate) from 25 states… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 27 publications
(78 reference statements)
1
11
0
Order By: Relevance
“…In short-lived disasters, this strategy has proven it's worth [11]. However, the COVID pandemic has shown that there may be a very steep price to pay when such an approach is taken over long periods of time: psychopathologies, which may express both during the acute phase [12,13] and after the event [14–16,17 ▪ ].…”
Section: What Resources Require Allocation?mentioning
confidence: 99%
“…In short-lived disasters, this strategy has proven it's worth [11]. However, the COVID pandemic has shown that there may be a very steep price to pay when such an approach is taken over long periods of time: psychopathologies, which may express both during the acute phase [12,13] and after the event [14–16,17 ▪ ].…”
Section: What Resources Require Allocation?mentioning
confidence: 99%
“…Although the findings from Burns et al (6) help to highlight the scope and breadth of this issue, one should recognize the limitations of the study by Burns et al (6). The results themselves may not be representative of the behavior, attributes, and responses of all physicians who care and cared for critically ill patients during the pandemic, as the majority of those who responded were male, university hospital-based physicians, who had been practicing for a mean of approximately 10 years.…”
mentioning
confidence: 98%
“…In this issue of Critical Care Medicine , Burns et al (6), on behalf of the Diversity-Related Committee of the Women in Critical Care interest group of the American Thoracic Society, assessed wellness and coping strategies in physicians who cared for critically ill adults and children during the COVID-19, via a survey of attending physicians who worked in adult and PICUs. They observed, similar in part to observations from others, that almost all physicians reported more time worked per month, a higher patient census under their care, increased physical and emotional exhaustion, and lower levels of professional fulfillment.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…They can throw light on where, how, and why hospital strain manifested and pinpoint potential contributors to patient harm and guide future research and action. Surveys have helped capture care variations (11) and providers’ coping strategies from burnout (12) during the pandemic. However, surveys have their own limitations: their results are as best as the survey tool used and the respondents surveyed.…”
mentioning
confidence: 99%